2021
DOI: 10.1080/00325481.2021.1873027
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of the COVID-19 pandemic: a cross-sectional study of online help-seeking Canadian men

Abstract: Purpose:The COVID-19 pandemic has had a profound impact on the lives of men. The present study investigated psychosocial impacts of the COVID-19 pandemic on a help-seeking sample of Canadian men, focusing on diverse aspects of their psychosocial well-being. Methods: A cross-sectional, open survey study design was used. Canadian adult men who were visiting an eHealth depression resource (HeadsUpGuys.org) were recruited to complete an online survey. Descriptive statistics, including means and standard deviations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 65 publications
2
48
0
1
Order By: Relevance
“…The aim of this research was to analyze the emotional impact of the pandemic on students, teachers, and administrative staff, and the extent to which the psychosocial aspects are able to characterize their affective states. In this sense, our research provides a global overview, analyzing the extent to which sociodemographic variables (Liang et al, 2020 ; Losada-Baltar et al, 2020 ; González-Tovar and Hernández-Rodríguez, 2021 ), the impact of COVID on the subjects' environment (Sandín et al, 2020 ), the psychosocial context of coexistence and perceived social support (Losada-Baltar et al, 2020 ; Sandín et al, 2020 ; Ogrodniczuk et al, 2021 ), characteristics related to the physical context during the quarantine (Sandín et al, 2020 ), labor conditions (Sandín et al, 2020 ; Zurlo et al, 2020 ). and the work-life balance (Bhumika., 2020 ; Wan Mohd Yunus, 2021 ) can characterize the emotional states of the subjects during the quarantine (Sandín et al, 2020 ; González-Tovar and Hernández-Rodríguez, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this research was to analyze the emotional impact of the pandemic on students, teachers, and administrative staff, and the extent to which the psychosocial aspects are able to characterize their affective states. In this sense, our research provides a global overview, analyzing the extent to which sociodemographic variables (Liang et al, 2020 ; Losada-Baltar et al, 2020 ; González-Tovar and Hernández-Rodríguez, 2021 ), the impact of COVID on the subjects' environment (Sandín et al, 2020 ), the psychosocial context of coexistence and perceived social support (Losada-Baltar et al, 2020 ; Sandín et al, 2020 ; Ogrodniczuk et al, 2021 ), characteristics related to the physical context during the quarantine (Sandín et al, 2020 ), labor conditions (Sandín et al, 2020 ; Zurlo et al, 2020 ). and the work-life balance (Bhumika., 2020 ; Wan Mohd Yunus, 2021 ) can characterize the emotional states of the subjects during the quarantine (Sandín et al, 2020 ; González-Tovar and Hernández-Rodríguez, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are examples from many countries highlighting a widespread deterioration in mental health. For example, Canadians were experiencing a decline in their mental health and coping due to COVID‐19 (Jenkins et al, 2021 ) and Ogrodniczuk et al ( 2021 ) found that 79.3% of Canadian men indicated that COVID‐19 negatively affected their mental health. Anxiety screenings, which consist of individuals' responses to online questions about self‐reported mental illness symptoms were 93% higher in the United States than pre‐pandemic levels (Mental Health America, 2020 ) and over 40% of the population in Italy and the United Kingdom were at risk for mental illness, defined as the conditional probability of being under high stress, anxiety and depression given economic vulnerability and negative economic shock (Codagnone et al, 2020 ).…”
Section: Stress and The Pandemicmentioning
confidence: 99%
“…Importantly, the study was conducted during the COVID-19 pandemic, even though a small number of COVID-19 cases existed in Beijing during the survey period [48], and study participants were limited to those who were not infected or did not have a COVID-19 infection history. The enforcement of COVID related measures such as closing borders or mandatory quarantine could potentially impact women's daily activities [49], the support resources at their disposal [50], as well as their actual abortion experience and associated psychological responses [51]. To determine the generalizability of our ndings, we subsequently compared demographic and reproductive characteristics of women included in this study to a national cross-sectional study of 79,954 women in China who had an induced abortion in 2013 (pre-COVID).…”
Section: Limitationsmentioning
confidence: 99%